PLANT RESIDUES AS AN ALTERNATIVE FOR SUBSTRATE COMPOSITION IN THE PRODUCTION OF Eucalyptus grandis SEEDLINGS - Martínez Hernández, Marileydy; Medeiros das Chagas Silva, Oclizio; Carvalho Diniz, Paloma; Pereira de Souza, Nicolas; Amaral de Melo, Lucas (Floresta, 2023)
Selecting constituents for substrate formulations is of fundamental importance for the production of quality seedlings. The objective of this work was to evaluate the initial growth of Eucalyptus grandis seedlings, using carbonized and fresh coffee husks, cattle manure, coconut fiber and carbonized rice husks as substrate constituents, in different combinations. As a control treatment, the commercial substrate Maxfértil was used. The experiment was set in a nursery, in a randomized block design, consisting of eight treatments and four replications, with a sample unit of 16 seedlings. To evaluate the quality of the seedlings formed, the biometric variables, and plant biomass were quantified and the characterization of the physical and chemical properties of the formulated substrates was also carried out, regarding the characteristics of the seedlings produced. Qualitative analyses were used, where the ease of removing the seedlings from the tube and the aggregation of the roots to the substrate were assessed. After data analysis, it was found that the use of coffee husks was adequate for the production of Eucalyptus grandis seedlings for most of the analyzed variables, with higher values than the seedlings formed in the control treatment. Thus, coffee husks are indicated as an alternative constituent of substrates for the production of seedlings of the referred species